Interlocking Nail Stabilisation of Humeral Fractures. Initial Experience in Seven Clinical Cases - Durall, I.; Diaz, M.C.; Morales, I. (Veterinary and Comparative Orthopaedics and Traumatology, 1994)
Seven cases of fracture of the humerus were stabilised by interlocking nailing. In six cases fixation was static, and in one dynamic. Healing of the fractures took place within a maximum of 16 weeks and return of functionality was complete within three weeks, with the exception of one case. The complications were: failure to insert the screws in the nail, partial loosening of a screw, and production of a new fracture at the distal end of the nail in the case with dynamic fixation.Seven humeral fractures were stabilised by interlocking nailing. Healing of bone took place in six cases.The complications involved were: failure to insert screws in the nail, loosening of the screws, and production of a fresh fracture at the distal end of the nail.
Keywords: Interlocking nail; humeral fractures; pin